Changes in physiological and antioxidant activity of indica rice seedlings in response to mannitol-induced osmotic stress - Sutee Chutipaijit (My University, 2016)
Changes in physiological and antioxidant activity of indica rice
Keywords: Osmotic shock; Food Quality and Safety Studies